2020
DOI: 10.1103/physrevd.101.084005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the gedanken experiment to destroy the event horizon of a regular black hole

Abstract: Recently, Li and Bambi proposed a hypothesis that the event horizon of a regular black hole can be destroyed because these objects have no gravitational singularity and therefore they are not protected by the weak cosmic censorship conjecture (WCCC). In this paper, to test their hypothesis, we perform the new version of the gedanken experiments proposed by Sorce and Wald to overcharge a near extremal static electrically regular black hole. After introducing the stability condition of the spacetime and the null… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Recently, Sorce and Wald proposed a new version of the thought experiment to destroy a nearly extremal Kerr-Newman black hole at the second-order approximation of the perturbation that comes from the matter fields [44], the result shows that the event horizon of the Kerr-Newman black hole cannot be destroyed. Using the method of Sorce and Wald, the systematic works of Jiang et al suggest that a series of black holes cannot be destroyed [45][46][47][48][49][50][51][52][53]. Another way of destroying the event horizon of a black hole to test the validity of the weak cosmic censorship conjecture is the scattering of a test classical field first proposed by Semiz [54], and further developed by others [55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sorce and Wald proposed a new version of the thought experiment to destroy a nearly extremal Kerr-Newman black hole at the second-order approximation of the perturbation that comes from the matter fields [44], the result shows that the event horizon of the Kerr-Newman black hole cannot be destroyed. Using the method of Sorce and Wald, the systematic works of Jiang et al suggest that a series of black holes cannot be destroyed [45][46][47][48][49][50][51][52][53]. Another way of destroying the event horizon of a black hole to test the validity of the weak cosmic censorship conjecture is the scattering of a test classical field first proposed by Semiz [54], and further developed by others [55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…The similar idea to Hubeny's in violating WCCC for Kerr black hole was proposed Jacobson and Sotiriou [9], for Kerr-Newman black hole were discussed in [10,11], and for magnetized Kerr black hole is investigated in [12]. The reconsideration of WCCC in the fashion of Hubeny [8] is not limited just to black holes in Einstein-Maxwell theory, but also beyond [13,14,15,16,17,18,19,20]. However, a newer version of checking WCCC by Sorce and Wald [21] shows that if the self-force and finite size effects are considered, then no such black hole destruction as illustrated in [8,9,11,12] can occur.…”
Section: Introductionmentioning
confidence: 81%
“…The result showed that after the perturbation, the WCCC for KN black holes is still satisfied. Furthermore, using this method, the WCCC for other kinds of black holes is demonstrated to be valid [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%